Identification of Potential Biomarkers in Peripheral Blood Supernatants of South African Patients with Syphilitic and Herpetic Uveitis. (17th February 2021) - Andreae, Corinna D.; Smit, Derrick P.; Makhoba, Nonjabulo S.; Kidd, Martin; Walzl, Gerhard; Chegou, Novel N.
ABSTRACT: Purpose : To identify potential diagnostic biomarkers for herpetic and syphilitic uveitis. Methods : Blood samples were collected from 92 uveitis patients. Concentrations of 47 biomarkers were evaluated in unstimulated Quantiferon supernatants using the Luminex platform. Results : Results showed 11 patients (12%) had herpetic uveitis, 11 (12%) syphilis, 40 (43.5%) other infectious causes, 16 (17.4%) established noninfectious causes and 14 (15.2%) were idiopathic. Biomarker analysis revealed three proteins (Apo-A1, Apo-CIII, CRP) that differed between syphilis and other causes. A three-marker biosignature (CCL4/MIP-1β, Apo-CIII and CRP) separated syphilis from other groups with AUC = 0.83 (95% CI: 0.68–0.98). Apo-CIII and CRP differed between herpetic cases and other groups ( p < .05). A three-analyte biosignature (Apo-A1, SAP and CRP) separated the herpetic group from other groups with AUC = 0.79 (95% CI: 0.65–0.93). Conclusion : We have identified candidate biomarkers with potential to differentiate between herpetic, syphilitic and other causes of uveitis. These results warrant further investigation in larger future studies.